WHAT IS THE CONDITION OF THE MINIMUM WAGE OF LAMPUNG PROVINCE IN 2016-2022 - Irwandi (Journal Management & Economics Review (JUMPER), 2023)
The research team behind this study set out to answer this question by looking at how employment rates in Lampung Province were affected by economic growth, unemployment, and provincial minimum wages. This survey takes a quantitative approach, collecting and analyzing secondary data from 2016 through 2022. The data was collected using a documented procedure, and then subjected to SPSS-based multiple regression analysis. This study found that in the municipalities of Lampung Province, the minimum wage did not have a statistically significant negative effect on employment. Reason being, if wages are raised, workers will have enough money to provide for their basic needs as well as the luxuries that make life worth living. If workers' diets improve, worker productivity will increase, resulting in increased production and firms will hire more workers for production.